An Experimental Study On Tubular Fluorescent And Led Lamps With Respect To Energy Performance And Visual Comfort - Manav, Banu; Erkin, Emre; Güler, Önder; Onaygil, Sermin (Znack Publishing House, Po Box 648, 10100 Moscow, Russia, 2013)
In the recent years, energy efficiency studies have been given priority in the field of lighting research. It is strictly advised to reduce energy consumption while maintaining visual quality, safety and comfort. Within those scope, the aim of this study is to evaluate energy performance and visual comfort of tubular LED lamps. Measuring and calculating illuminance, uniformity, power demand, total harmonic distortion and power factor of tubular fluorescent and LED lamps allow a comparison of the two lighting installations via quantitative methods. Qualitative data is evaluated by a visual task designed to evaluate the room impression and perception of changes in the lighting systems. 30 randomly selected employees participated in the study. Results suggest that, tubular LED lamps are similar to tubular fluorescent lamps in terms of lighting quality. The evaluated data on illuminance, glare and visual appearance indicate that there is no difference in visual perception between lamp types. On the other hand, 22.8% of energy saving ratio could be achieved with the technology used in this field test; however, this ratio could be more than 60% with inevitable development in LED technology. As a result, tubular LED lamps can be used as an alternative to tubular fluorescent lamps in terms of energy efficiency.
Keywords: tubular fluorescent lamps; tubular LED lamps; energy performance; energy saving; lighting quality; visual comfort